2003
DOI: 10.1034/j.1600-0714.2003.t01-1-00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor and epidermal growth factor reverse impaired ulcer healing of the rabbit oral mucosa

Abstract: Basic FGF may be effective for refractory oral mucosal lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 26 publications
2
79
0
2
Order By: Relevance
“…Fujisawa et al 111) reported that healing of acetic acid ulcers induced in rabbit oral mucosa was delayed after removal of submandibular glands or subcutaneous injection of cisplatin and peplomycin sulfate. Such delayed healing by gland removal or drug administration was reversed with either systemic treatment with bFGF and EGF or topical application of bFGF.…”
Section: Growth Factors Epidermal Growth Factor (Egf)mentioning
confidence: 99%
“…Fujisawa et al 111) reported that healing of acetic acid ulcers induced in rabbit oral mucosa was delayed after removal of submandibular glands or subcutaneous injection of cisplatin and peplomycin sulfate. Such delayed healing by gland removal or drug administration was reversed with either systemic treatment with bFGF and EGF or topical application of bFGF.…”
Section: Growth Factors Epidermal Growth Factor (Egf)mentioning
confidence: 99%
“…Until now, epidermal growth factor (EGF) studies have been performed only for oral keratinocytes, but not for oropharyngeal keratinocytes. For example, it was found that EGF promotes the proliferation of keratinocytes isolated from gingival tissue of the rabbit in vitro [Fujisawa et al, 2003]. Furthermore, it was discovered that when the oral mucosa is injured, a physiological concentration of EGF in saliva stimulates the proliferation and migration of oral epithelial cells for wound healing [Ohshima et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Acetic acid is applied after either a sialoadenectomy or intravenous treatment with cisplatin and peplomycin sulfate. Both procedures create a state of impaired healing from the acetic acid injury and, ultimately, ulceration at the injury site (Fujisawa et al, 2003). Most preclinical studies focus on oral mucositis; however, a few do measure intestinal mucositis and loss of structural integrity of intestinal crypts.…”
Section: Preclinical Studies On Treatment Of Mucositis and Associatedmentioning
confidence: 99%
“…They showed that systemic EGF accelerated mucosal healing. However, topical EGF application did not significantly accelerate wound healing (Fujisawa et al, 2003). A clinical trial evaluated a recombinant human EGF oral spray in 58 patients with oral mucositis induced by intensive chemotherapy followed by stem cell transplant.…”
Section: Epidermal Growth Factormentioning
confidence: 99%